APPLICATION OF RESPONSE SURFACE METHODOLOGY FOR ANTIOXIDANT EVALUATION OF TANACETUM UMBELLIFERUM BOISS; TARGETING GOUT AND HYPERURICEMIA - Rabia Zahid; Muhammad Akram; Hafiz Muhammad Asif; Sultan Ayaz; Abid Rashid (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Oxidative degeneration of cells and tissues is the common concern of scientific research and debate in medical sciences round the globe. Oxidative stress in body is reflected by generation of reactive oxygen species (ROS) that are free radicals with least count of unpaired electrons having high reactivity. Imbalance between biological system and ROS is responsible for degeneration of tissues and became toxic to induce misfolding of protein, activation of glia cell, mitochondrial malfunction and apoptosis of cell. One of the susceptible mechanisms for degenerative changes of joints is generation of ROS. Traditionally claimed Tanacetum umbelliferum is an enduring member of the “Asteraceae” family, and defeats the manifestations of arthritic and gouty conditions where one of the most probable underlying mechanisms is free radical scavenging (FRS). The current research was planned to find out FRS capacity of T. umbelliferum using in vitro antioxidant activity by DPPH assay and effect of the different solvents (ethanol, chloroform, 1 butanol, n-hexane) on the extraction of bioactive chemicals. The experimental design was determined at optimum level using response surface methodology technique. Phytochemical screening declared the presence of alkaloids, flavonoids, phenols and glycosides that are suspected to be responsible for antioxidant potential. The HE crude extract demonstrated more activity than the fractions, at 3.1 mg/mL, the percentage inhibition was determined as 99.9, 94, 88.4, 80 and 71% for ascorbic acid, crude HE extract, and 1-butanol, chloroform, n-hexane fractions respectively, where the tapering of dose sequentially reduced the inhibition percentage. As lower IC50 reflects higher DPPH scavenging activity. Therefore, it is deducted that polar phytochemicals are potent free radical scavengers and being constituted with these phytochemicals T. umbelliferum is proven to be the effective, safe and potent option for management of arthritic disorders such as gout and hyperuricemia.